Product Costing and Pricing - Banker, Rajiv D.; Hughes, John S. (The Accounting Review, 1994)
[Recently, management accountants have focussed attention on the appropriate treatment of costs associated with resources committed to support activities which do not vary proportionally to production once initial capacities have been set. In one typical case, it is assumed that costs of committed resources will be incurred irrespective of actual usage, and increasing initial capacities to accommodate unexpected demand involves penalties above normal costs. There are at least two important issues that arise in such a case: (1) how should costs of resources committed to, or subsequently required by, support activities enter into pricing and capacity decisions, and (2) what information should the accounting system provide to marketing and production in order to implement those decisions. Our objective in this paper is to address these two issues. The basic tension which underlies both pricing and capacity decisions is between the nonrecoverable cost of adding capacity before demand becomes known, and the expected penalty-adjusted cost of doing so after demand becomes known. In regard to the first issue, we find in our setting that only normal cost enters into pricing rules established at the time initial capacities are set. (Penalties for exceeding initial capacities are implicit in that for the marginal unit of each activity, normal cost equals expected penalty-adjusted cost.) Findings on the second issue are that the product costing system can be designed without knowledge of demand parameters; the marketing manager only requires activity-based unit costs provided by that system, along with knowledge of demand parameters, to make pricing decisions which are optimal from a firm-wide standpoint; and the production manager only needs expected demand from marketing, along with knowledge of the distribution of random demand shocks, and cost and production parameters, to make initial capacity decisions. The economic sufficiency of the activity-based unit cost in pricing decisions is in the spirit of Amershi et al. (1989), while the equivalence of marginal cost, normal cost, and expected penalty-adjusted cost of under-capacity bear similarity to results in studies by Miller and Buckman (1987), Whang (1989) and Hansen and Magee (1993). The main distinctions between these studies and ours lie in assumptions regarding production functions, the nature of information asymmetries, and our incorporation of pricing decisions as well as capacity decisions.]